CircCLTH promotes skeletal muscle development and regeneration. Issue 13 (9th December 2022) - Chen, Mengjie; Liu, Qingyou; Song, Mingming; Liu, Xingyu; Huang, Kongwei; Zhong, Dandan; Chen, Yaling; Jiang, Mingsheng; Sun, Junming; Ouyang, Yiqiang; Sooranna, Suren R; Shi, Deshun; et al.
ABSTRACT: Buffalo holds an excellent potential for beef production, and circRNA plays an important role in regulating myogenesis. However, the regulatory mechanism of circRNAs during buffalo skeletal muscle development has not been fully explored. In this study, circRNA expression profiles during the proliferation and differentiation stages of buffalo myoblasts were analysed by RNA-seq. Here, a total of 3, 142 circRNAs candidates were identified, and 110 of them were found to be differentially expressed in the proliferation and differentiation stages of buffalo myoblast libraries. We focused on a 347 nt circRNA subsequently named circCLTH. It consists of three exons and is expressed specifically in muscle tissues. It is a highly conserved non-coding RNA with about 95% homology to both the human and the mouse circRNAs. The results of cell experiments and RNA pull-down assays indicated that circCLTH may capture PLEC protein, promote the proliferation and differentiation of myoblasts as well as inhibit apoptosis. Overexpression of circCLTH in vivo suggests that circCLTH is involved in the stimulation of skeletal muscle regeneration. In conclusion, we identified a novel noncoding regulator, circCLTH, that promotes proliferation and differentiation of myoblasts and skeletal muscles. Highlights: A new highly conserved circRNA was identified during muscle development CircCLTH promotes proliferation and differentiation of myoblasts CircCLTH promoted muscle damage repair in mice CircCLTH may target the PLEC protein GRAPHICAL ABSTRACT: uf0001